PUBLIC INTEREST AND ADMINISTRATIVE LEGAL PROCEEDINGS - D. Tumanov (BRICS Law Journal, 2016)
This paper focuses attention on the issue of the definition of public interest, in particular, on the fact that the public interest lies in the organization of the most efficient protection system, one that also protects against possible abuse of power by the State itself. The paper argues that the adoption of the Administrative Court Proceedings Code of the Russian Federation was a mistake and demonstrates that the mechanisms implemented in the code to protect public interests are inefficient.